A Road Map for the Identification of the Diffuse Interstellar Band Carriers. Issue Volume 9:Issue S297(2013) (21st February 2014) - Cox, N. L. J.; Cami, J.
Abstract: We present a road map of several research avenues leading to the identification of the diffuse interstellar band carriers. The proposed programs represent some consensus among the DIB community, and will certainly take many years to complete. However, the scientific payoff will be huge, and will ultimately lead to the solution of the DIB problem.